The effect of hippocampal NR2B-containing NMDA receptors on chronic cognitive dysfunction in rats with temporal lobe epilepsy - Xiaoqing Luo; Cheng Li; Xiaoli Yu; Guangtao Kuang; Xiaolu Wang; Jufang Liang; Jun Jiang (Acta Epileptologica, 2023)
Abstract Background We have previously reported that hippocampal long-term potentiation (LTP) was suppressed in temporal lobe epilepsy (TLE) rats. The N-methyl-D-aspartic acid receptors containing 2B subunit (NR2B-NMDARs) are indispensable to induce the LTP of hippocampus. However, it is still unknown whether the NR2B-NMDARs are implied with the cognitive dysfunction in TLE rats. Methods The TLE model was lithium chloride-pilocarpine (li-pilo) model. Morris water maze test was used to evaluate the cognitive function of epileptic rats. Expression of hippocampal NR2B-NMDAs was evaluated by western blotting. Stereotactic injection of NMDA, an agonist of NR2B-NMDARs, into the hippocampus of TLE rats was used to investigate the role of NR2B-NMDARs on cognitive dysfunction. Results Cognitive function TLE rats was significantly reduced compared with controls in the Morris water maze test (P < 0.05). Western blotting data showed the down-expression of hippocampal NR2B-NMDARs and p-NR2B in TLE rats compared with the control (P < 0.05). In addition, hippocampal stereolocalization of NMDA injection improved partially the learning and memory in TLE rats (P < 0.05). Conclusions Down-expression and low activity of hippocampal NR2B-NMDARs may be implied with chronic cognitive dysfunction in TLE rats.